Penerapan Supervisi Akademis Kepala Sekolah Dalam Upaya Meningkatkan Kinerja Guru Perihal Pengembangan Evaluasi Hasil Belajar Di Smp Negeri Satu Atap Bilal Tahun Pelajaran 2020/2021 - Felix Lafe Labaona (Simpati, 2023)
The feasibility of teaching is not only measured based on formal education but also must be measured based on how the teacher's ability in teaching and material mastery sessions, mastering, choosing and using methods, media and learning evaluation. The purpose of this study is to increase teacher performance in developing evaluation of learning outcomes through Academic Supervision at Bilal One Roof Public Middle School, East Adonara District, 2020/2021 Academic Year. The effectiveness of implementing school principal academic supervision in improving teacher performance in developing evaluations of learning outcomes at Bilal One Roof Public Middle School, Adonara Timur District for the 2020/2021 academic year. This type of research is school action research through the implementation of the Principal's academic supervision including planning, action, observation and reflection. The results of the study show (1) the increase in teacher performance by the principal through the academic supervision of the principal shows an increase in each round. (2) The activities of the school principal show that coaching activities through the academic supervision of the school principal are useful and can help teachers more easily understand the concept of the teacher's role and function so that teacher performance can increase.